2019
DOI: 10.2460/ajvr.80.11.1043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bite depth of an epitendinous suture on the biomechanical strength of repaired canine flexor tendons

Abstract: OBJECTIVE To determine effects of bite depth for placement of an epitendinous suture on the biomechanical strength and gap formation of repaired canine tendons. SAMPLE 48 superficial digital flexor tendons (SDFTs) obtained from 24 canine cadavers. PROCEDURES Tendons were assigned to 3 groups (16 tendons/group). Each SDFT was transected and then repaired with a continuous epitendinous suture placed with a bite depth of 1, 2, or 3 mm for groups 1, 2, and 3, respectively. Specimens were loaded to failure. Fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…Patterns include simple continuous, Silfverskiöld crossstitch, and interlocking horizontal mattress patterns, which have been shown to increase construct strength 2.5-fold compared with core suture use alone. [16][17][18][19][20] Improvement in construct strength has also been demonstrated by positioning suture bites at a great distance from the transection site. 17 Increasing the bite depth of suture into the tendinous core has also been shown to confer significant biomechanical advantages to experimental canine constructs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns include simple continuous, Silfverskiöld crossstitch, and interlocking horizontal mattress patterns, which have been shown to increase construct strength 2.5-fold compared with core suture use alone. [16][17][18][19][20] Improvement in construct strength has also been demonstrated by positioning suture bites at a great distance from the transection site. 17 Increasing the bite depth of suture into the tendinous core has also been shown to confer significant biomechanical advantages to experimental canine constructs.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] In the veterinary literature, researchers have reported superior biomechanical strength at the repair site while reducing gap formation compared with core suture use alone. [16][17][18][19] Gelberman et al 3 demonstrated that, in dogs, gap formation >3 mm increased healing times, decreased repair site strength, and increased the relative risk for tendon rerupture during the first 6 weeks after surgical intervention. Several ES suture patterns have been evaluated for use in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Depth of epitendinous suture placement within the body of the tendon also served as a limitation as it has been previously shown that differing levels of penetration significantly affect the strength of the repair. 13 It should be noted that core suture size utilized in this study was larger than those typically used for human flexor zone II tendon repair. Suture size may have contributed to increased loads to failure observed in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Ideal characteristics of a primary suture tendon repair include, but are not limited to, a simple technique, reliable fixation method, provision of adequate tensile strength, minimal gap formation, good tendon apposition and conservation of tendon vascularity. 24 Epitendinous repairs provide many of these attributes and their importance has been repeatedly demonstrated as they provide up to a 50% increase in repair site strength [10][11][12][13][14][15]25 and resistance to gap formation by 165% over core suture use alone. 26 Results of the present study are in accordance with previous investigations, where IHMES addition to a core 3LP suture significantly increased mean yield, peak and failure forces by 180, 200 and 200%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation